Algoritma Apriori Untuk Pola Penjualan Pada Kedai Kopi Studi Kasus: Kedai Kopioko - Juliano, Aryo; Rasim, Rasim; Sugiyatno, Sugiyatno (Journal of Students‘ Research in Computer Science, 2022)
Effective promotion can increase sales figures. One way is to identify market conditions, namely about consumer purchasing tastes, which can be observed through consumer purchase transaction data. In recent years, transaction data has been widely used as research material, which aims to build some new information related to sales patterns to help manage future business development. In this study, the a priori algorithm method was used to determine sales patterns. The results obtained from the experiments carried out that the application of data mining using yahoo a priori with the association rule method can run well and produce two association rules, by changing the minimum support and confidence parameters. After the experiment using the apriori algorithm, it was found that the combination of menu items that can be made for sales patterns or the development process uses the racist Kopioko package menu, potatoes with a value of 60.34%, and racist Kopioko, Agung with a value of 54.88